Analisa Lokasi, Desain Produk dan Harga Produk terhadap Keputusan Pembelian Konsumen pada Toko Emas Kausar Solo - Zulva Nur Fadillah; Eny Kustiyah; Sudarwati Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2019)
Abstrak In facing a free market with a lot of competition and also a dynamic business development, the company must conduct marketing activities that are right on target and change orientation by serving consumers, continuing to issue products and handling competitors. Of course in running this business there is intense competition so that what is done by companies in marketing activities must further improve the product and be directed more precisely to the target by prioritizing service to consumers, because most consumers prefer to prioritize in service and expect an attractive product. So that the business of gold jewelery has very high potential, because it is for investment or savings in people's lives. This study aims to determine the effect of location, product design, and product prices on purchasing decisions at the Kausar Solo Gold Shop. This research used quantitative descriptive method. This study uses samples of 100 respondents and an infinite population. The results of this study indicate that location variables negatively affect consumer purchasing decisions, while product design variables and product prices have a significant positive effect on consumer purchasing decisions.